ENHANCING SPEAKING PROFICIENCY THROUGH THE COMMUNITY LANGUAGE LEARNING APPROACH: AN EXPERIMENTAL STUDY AMONG EFL LEARNERS - Arfian Hikmat Ramdan; Fitri Wulandari; Cholida Nur Fajri; Gadis Herningtyasari; Cok Istri Agung Sri Wulandari; Lidya Cristina Febriani Situmorang (PT. Jurnal Center Indonesia Publisher, 2026)
The aim of this research was to investigate: (1) the application of the Community Language Learning (CLL) model on students’ speaking competence, (2) the students’ speaking competence before and after the implementation of the CLL model, and (3) whether there is a significant effect of the CLL model on students’ speaking competence. The population of this study consisted of 248 tenth-grade students at SMA Negeri 5 Padangsidimpuan. Using systematic sampling, a total of 35 students were selected as the sample. This research employed an experimental method. Data were collected through observation and speaking tests, and the results were analyzed using a paired-sample t-test. The findings revealed that the application of the CLL model on students’ speaking ability scored 3.6, categorized as “Very Good”. The students’ mean speaking score before the implementation of CLL was 78.51 (“Good”), which increased to 83.42 (“Very Good”) after the treatment. The t-test calculation yielded a t-value of 7.15, which exceeds the critical t-value of 2.03 at a 5% significance level (df = 35). Therefore, it is concluded that there is a statistically significant effect of the Community Language Learning model on students’ speaking competence among tenth-grade students at SMA Negeri 5 Padangsidimpuan.